ENGLISH VOCABULARY TRAINING IN THE FIELD OF CULINARY FOR CHILDREN AT THE NAUNGAN KASIH ENDE ORPHANAGE - Ota, Maria Kristina; Kara, Yuliana Maria D Karmel; Separ, Fransiskus Maria; Kasimo, Julius Yoseph; Djou, Ana Maria Gadi; Amrin, Sayful; Ma, Stefanus H. G.; Jedho, Fransiska; Hayon, Emanuel Basa; Zaun, Bernadeta Mayelanti (LPPM Universitas Flores, 2024)
A community service program (PKM) aims to improve children's mastery of English vocabulary related to the culinary world at the Naungan Kasih Ende Orphanage. The program was implemented through three stages: preparation, implementation, and evaluation. The preparation stage includes Observation, Coordination with the orphanage, Preparation of training materials, and Preparation of learning media. The implementation stage, a hands-on learning experience, involves giving a pre-test, introducing and explaining basic culinary English vocabulary, having game sessions, doing writing and speaking practice activities, and practising cooking. The evaluation stage includes a post-test, evaluation of program effectiveness, collection of feedback, and preparation of reports. Through this PKM program, it is hoped that the orphanage children can improve their mastery of English vocabulary in the culinary field, which can help them learn, prepare to enter the world of work in the culinary industry and motivate them to continue developing their culinary-related English skills.